Efektivitas Implementasi Undang-Undang Perlindungan Data Pribadi terhadap Perlindungan Konsumen pada Platform Financial Technology di Indonesia - Ayumi Kartika Sari; Merry Roseline Pasaribu (Cattleya Darmaya Fortuna, 2026)
The rapid growth of Financial Technology (Fintech) has transformed the delivery of digital financial services by providing greater accessibility, efficiency, and convenience for consumers. However, this advancement has also increased the risk of personal data breaches, unauthorized data processing, and cyber threats that may undermine consumer trust. The enactment of Law Number 27 of 2022 concerning Personal Data Protection (PDP Law) represents a significant milestone in strengthening Indonesia's legal framework for safeguarding personal data and enhancing consumer protection in the digital financial ecosystem. This study aims to analyze the effectiveness of the implementation of the PDP Law in protecting consumers using fintech platforms and to identify the challenges encountered in its enforcement. This research employs a normative legal research method using statutory and conceptual approaches. The data were collected through a comprehensive literature review of laws and regulations, academic publications, scientific journals, and official documents related to personal data protection and fintech regulation. The findings indicate that the implementation of the PDP Law has improved legal certainty by clearly defining the rights of data subjects, the obligations of personal data controllers, and legal accountability mechanisms in cases of personal data breaches. Nevertheless, its effectiveness remains constrained by several factors, including the limited compliance of some fintech providers, inadequate regulatory supervision, insufficient public awareness of personal data rights, and difficulties in enforcing legal sanctions against cross-border violations. Therefore, stronger inter-agency coordination, enhanced regulatory oversight, stricter administrative and criminal sanctions, and continuous public education are essential to ensure effective implementation of the PDP Law. This study is expected to contribute to the development of legal policies on personal data protection and support the establishment of a secure, trustworthy, and consumer-oriented fintech ecosystem in Indonesia.